2021
DOI: 10.3389/fmicb.2021.779885
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Linezolid Plus Fosfomycin Against Vancomycin–Resistant Enterococcus faecium in a Hollow Fiber Infection Model

Abstract: The optimal therapy for severe infections caused by vancomycin-resistant Enterococcus faecium (VREfm) remains unclear, but the combination of linezolid and fosfomycin may be a good choice. The 24-h static-concentration time-kill study (SCTK) was used to preliminarily explore the pharmacodynamics of linezolid combined with fosfomycin against three clinical isolates. Subsequently, a hollow-fibre infection model (HFIM) was used for the first time to further investigate the pharmacodynamic activity of the co-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“… 56 Wang et al further found that the downregulation of the virulence of fosfomycin was concentration-dependent on the fosfomycin-resistant mutants obtained from the hollow fiber model. 24 Subsequently, RT-qPCR revealed that the overall virulence factor of the mutant decreased, with cylA and esp showing a decreasing trend on average, while asaL showed a slightly increasing trend at NO.24. A similar situation was found in previous studies of daptomycin-resistant methicillin-resistant Staphylococcus aureus and artificially induced Streptococcus that acquired daptomycin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 Wang et al further found that the downregulation of the virulence of fosfomycin was concentration-dependent on the fosfomycin-resistant mutants obtained from the hollow fiber model. 24 Subsequently, RT-qPCR revealed that the overall virulence factor of the mutant decreased, with cylA and esp showing a decreasing trend on average, while asaL showed a slightly increasing trend at NO.24. A similar situation was found in previous studies of daptomycin-resistant methicillin-resistant Staphylococcus aureus and artificially induced Streptococcus that acquired daptomycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Thus, the difference in treatment may be related to this hypothesis, as shown by Wang’s study; VRE virulence gene expression (especially acm ) and mortality of G. mellonella decreased with an increase in fosfomycin resistance, and virulence of the strain presumably decreased with an increase in fosfomycin resistance. 24 In addition, competition of Enterococcus strains to acquire fosfomycin resistance has not been reported yet. Studies on Enterococcus have mostly focused on in vitro rather than in vivo competition.…”
Section: Introductionmentioning
confidence: 99%
“…Fosfomycin resistance develops readily in vitro but less so in vivo. This discordance, at least partly, can be attributed to the function of the immune system in vivo and the lower likelihood that fosfomycin was selected in acidic environments [ 28 ]. At present, the temperature, sampling, and pump flow of the whole system can be controlled through computer to improve the experimental efficiency [ 9 ].…”
Section: Construction and Application Of Hollow Fiber Infection Modelmentioning
confidence: 99%
“…An increasing number of reports on the isolation of resistant pathogens combined with a weak antibiotic pipeline suggests that optimization of antibiotic therapy should be aimed at the suppression of resistance [ 37 ]. However, previous studies are limited by the continuous antibiotic concentration of more than 24 h, which is difficult to guide clinical rational drug use, and it is more difficult to explain the development of drug resistance from a quantitative perspective [ 28 ]. As an in vitro model, HFIM can determine when and at what dosage bacteria develop resistance and study the mechanism of resistance by related genetic testing techniques.…”
Section: Construction and Application Of Hollow Fiber Infection Modelmentioning
confidence: 99%
“… 13 , 14 We also got the conclusion that, for VRE strains, neither linezolid nor fosfomycin monotherapy inhibited amplification of the resistant sub-populations, and the development of fosfomycin resistance was at the expense of the virulence of VRE fm . 15 Fosfomycin plus linezolid or tigecycline showed synergism on VRE in time-kill studies of approximately 10% and 30%, respectively. 16 The combination of oritavancin and fosfomycin increased drug susceptibility and showed a synergistic effect in 80% of isolates and an additive effect in the remaining isolates.…”
Section: Introductionmentioning
confidence: 95%